Enhanced catalytic activity of nanostructured, A-site deficient (La0.7Sr0.3)(0.95)(Co0.2Fe0.8)O3-delta for SOFC cathodes - Celikbilek, Ozden; Thieu, Cam-Anh; Agnese, Fabio; Cali, Eleonora; Lenser, Christian; Menzler, Norbert H.; Son, Ji-Won; Skinner, Stephen J.; Djurado, Elisabeth (ROYAL SOC CHEMISTRY, 2019)
Lower operating temperatures (<= 650 degrees C) of solid oxide fuel cells (SOFCs) are sought in order to decrease the system costs and improve material compatibility and durability issues. Here, we report A-site deficient (La0.7Sr0.3)(0.95)(Co0.2Fe0.8)O3-delta (LSCF) perovskite film as a potential high-performance cathode with microstructural details at the nanometre length scale. This cathode exhibits area specific resistance values of as low as 0.037 and 0.1 omega cm(2) in a symmetrical cell and peak power densities of 1.4 and 1.0 W cm(-2) in a Ni/YSZ anode-supported cell at 650 and 600 degrees C, respectively. These values are among the highest reported data for LSCF-type cathodes. X-ray diffraction and electron microscopy analyses revealed a closely related two-phase perovskite structure for LSCF and a well-dispersed, nanoscale B-site spinel phase (CoFeOx) decorating the LSCF surfaces. Detailed investigations were carried out to correlate the surface to bulk elemental composition changes on the film, the catalytic activity of the spinel phase and the crystal structures of the constituents with the oxygen reduction reaction (ORR) kinetics. The oxygen transport parameters calculated from the electrochemical impedance spectra indicate an increase by one-to-two-orders of magnitude in the oxygen surface-exchange coefficient in comparison to nominally stoichiometric, state-of-the-art La0.6Sr0.4Co0.2Fe0.8O3-delta. Such substantial improvements in the electrode performance were attributed to the catalytically active B-site spinel phase precipitated as a result of the A-site deficiency and to the very high active surface area of the film.
Keywords: OXIDE FUEL-CELLS; OXYGEN REDUCTION REACTION; SR SURFACE SEGREGATION; THIN-FILM; ELECTROCHEMICAL PERFORMANCE; PHASE-STABILITY; TEMPERATURE; LA0.6SR0.4CO0.2FE0.8O3-DELTA; PEROVSKITE; ELECTROLYTE